GEN-Z MUSLIMS, SOCIAL MEDIA AND FORMLESS-SPIRITUAL: An Explorative Study of Mosque Youth in Medan City - Ziaulhaq Hidayat; Hasan Matsum; Azhari Akmal Tarigan (Jurnal Sosiologi Agama, 2023)
The article discusses spiritual understanding in the Gen-Z Muslim group, which is explored through Mosque Youth in Medan City. Spiritual issues for the Gen-Z Muslim group are considered important because they are believed to be able to bring a more guided direction. This study poses research questions about who Gen-Z Muslims are, what spiritual sources and how Gen-Z Muslim groups understand spiritual forms. The research method uses a qualitative method that describes a phenomenon in a descriptiveanalytical manner. This type of research is explorative, which seeks to deepen knowledge or discover new theories. The primary source of data is Mosque youth in Medan City. Data collection by observation, focus group, and documentation. Then, data analysis was done through reduction to summarize the data found to be grouped and presented through in-depth analysis. This research found that Gen-Z Muslims, as a group of youth mosques which are still students, gain religious knowledge from recitation and involvement with religious organizations and are shaped by social media. Sources of spiritual knowledge still need to be more authoritative. Finally, the research confirms that Gen -Z Muslims spiritual does not have a clear form because not resourced from resource authoritative.